AN ANALYSIS OF THE MAIN CHARACTER'S SWEARING IN DEADPOOL (2016) - Zagoto, Rafik Joshuan; Sri Adnyani, Ni Luh Putu; Agustin, Dewa Ayu Eka (Sekolah Tinggi Bahasa Asing Prayoga Padang, 2025)
This study analyzes the types and motivations of swearing uttered by the main character, Wade Wilson, in the movie Deadpool (2016). The research adopts a sociolinguistic approach using a qualitative method. The results reveal six types of swearing: abusive, idiomatic, dysphemistic, cathartic, emphatic, and humorous, and nine motivations, including storytelling, emphasis, emotional release, habit, normality, intimacy, vulnerability, personality, and shock value. The findings indicate that the main character’s swearing serves not only to express anger but also to display humor, emotional depth, and identity. The study concludes that swearing in Deadpool functions as a sociolinguistic tool reflecting the character’s emotional state and social context within the film.